(untitled) (Historia, 2021)
1. Van Tonder. dr . J . J . . Sewentien Perd- en Ruitermonumente in Suid-Afrika 2. Kennedy. R . F . . The Heart of a City, a History of the Johannesburg Public Library Williams. E . C .. Anne of Denmark 3. Greig. Doreen: A Guide to Architecture in South Africa 4. Dickens. A . G . en Davies. A.: Documents of Modern History 5. Smail. J . L .. Those Restless Years 6. Hardie. F . . The Political Influence of the British Monarchy 1868-1952 7. Green. L . G .. A Taste of South Easter 8. De Maumi. R .. The Franco-Prussian War 9. Asiegbu. J . U . J . . Slavery and Politics of Liberation 1787-1861 10. Preston. A.: The South African Diaries of Sir Garnet Wolseley